The prognostic factors in acute myeloid leukaemia with double‐mutated CCAAT/enhancer‐binding protein alpha (CEBPAdm). (10th March 2022) - Wei, Hui; Zhou, Chunlin; Liu, Bingcheng; Lin, Dong; Li, Yan; Wei, Shuning; Gong, Benfa; Zhang, Guangji; Liu, Kaiqi; Gong, Xiaoyuan; Fang, Qiuyun; Liu, Yuntao; et al.
Summary: The prognostic factors to stratify acute myeloid leukaemia (AML) with double‐mutated CCAAT/enhancer‐binding protein alpha ( CEBPA dm) into different risk groups remains to be determined. In this retrospective study, we evaluated 171 consecutive patients with newly diagnosed AML with CEBPA dm by a Cox proportional hazards regression model. In univariate analyses, colony stimulating factor 3 receptor ( CSF3R ) and Wilms tumour 1 ( WT1 ) mutations were associated with poor relapse‐free survival (RFS). The induction regimens including homoharringtonine (omacetaxine mepesuccinate) or intermediate‐dose cytarabine was associated with favourable RFS and overall survival (OS). The induction regimen including both homoharringtonine and intermediate‐dose cytarabine was associated with the most favourable RFS (3‐year RFS 84.7%) and OS (3‐year OS 92.8%) compared to the conventional cytarabine and daunorubicin regimen (3‐year RFS 27.7%, hazard ratio [HR] 0.126, 95% confidence interval [CI] 0.051–0.313, Wald p < 0.001; and 3‐year OS 56.4%, HR 0.179, 95% CI 0.055–0.586, Wald p = 0.005). In multivariate analyses, the induction regimen including intermediate‐dose cytarabine (HR 0.364, 95% CI 0.205–0.646, Wald p < 0.001) and CSF3R mutations (HR 2.667, 95% CI 1.276–5.572, Wald p = 0.009) were independently associated with RFS. Taken together, we found that induction regimen and CSF3R mutations were independent prognostic factors for AML with CEBPA dm.